THE ROLE OF LEGAL CULTURE IN SOCIETY'S CULTURAL DEVELOPMENT - Norkulov Dustmurad Toshpulatovich (Scholar Express Journal, 2023)
Due to the creative activities of people, culture, that is, cultural existence and socio-material, spiritual, political and legal cultures arise. Culture, that is, the results of the creative activity of cultural existence, should be consumed and used as the main part of cultural existence. Otherwise, the entire cultural entity will remain inactive. As social activity is a way of life of a whole cultural entity, legal activity is also a way of life of legal culture
Keywords: Legal Culture; Culture; Legal Activity